2008
DOI: 10.1007/s12031-008-9144-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex I Subunits are Altered in Rats with Neonatal Ventral Hippocampal Damage but not in Rats Exposed to Oxygen Restriction at Neonatal Age

Abstract: Several independent lines of evidence suggest mitochondrial dysfunction in schizophrenia in brain and periphery, including mitochondrial hypoplasia, dysfunction of the oxidative phosphorylation system, and altered mitochondrial-related gene expression. In an attempt to decipher whether mitochondrial complex I abnormality in schizophrenia is a core pathophysiological process or is attributable to medication, we studied two animal models of schizophrenia related to the neurodevelopmental hypothesis of this disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(78 reference statements)
1
5
0
2
Order By: Relevance
“…Mitochondrial dysfunctions have been demonstrated to lead to the generation of reactive oxygen species or to induce apoptosis mechanisms, which may sustain neurotoxic damage and have been implicated in schizophrenia pathophysiology (Ben‐Shachar,2002; Rezin et al,2009). Increased activity and protein expression of mitochondrial complex I have been found in schizophrenics and in an animal model of schizophrenia (Ben‐Shachar et al,2009; Rosenfeld et al,2011), and a correlation between increased mitochondrial complex I activity in platelets and increased glucose uptake in brain has been described for schizophrenic subjects showing prominent positive symptoms (Ben‐Shachar et al,2007). Increased mitochondrial complex I activity and oxidative damage have been found in selected rat brain areas after subchronic or acute administration of subanesthetic doses of ketamine, respectively (de Oliveira et al,2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunctions have been demonstrated to lead to the generation of reactive oxygen species or to induce apoptosis mechanisms, which may sustain neurotoxic damage and have been implicated in schizophrenia pathophysiology (Ben‐Shachar,2002; Rezin et al,2009). Increased activity and protein expression of mitochondrial complex I have been found in schizophrenics and in an animal model of schizophrenia (Ben‐Shachar et al,2009; Rosenfeld et al,2011), and a correlation between increased mitochondrial complex I activity in platelets and increased glucose uptake in brain has been described for schizophrenic subjects showing prominent positive symptoms (Ben‐Shachar et al,2007). Increased mitochondrial complex I activity and oxidative damage have been found in selected rat brain areas after subchronic or acute administration of subanesthetic doses of ketamine, respectively (de Oliveira et al,2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that examined brain tissue in schizophrenia patients reported an increase in activation of the mitochondrial complex, as compared to controls [ 6 , 7 ], whereas others reported a decrease [ 8 , 9 ]. Location and function of the brain tissue examined were important in the formation of these results.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the latter, a similar age‐dependent dynamic of complex I subunits protein levels (NDUFV1, NDUFV2 and NDUFS1) in the PFC of early in life lesion and non‐lesion rats was reported. Thus, prepubertal ventral hippocampus lesions, which resulted in a schizophrenia‐like behavioural phenotype, suppressed age‐dependent increases in these protein . The inverse tendency in the expression of genes in the MTR treated rats, was not a global rearrangement of the whole transcriptome, but was rather specific.…”
Section: Discussionmentioning
confidence: 91%